Innovative Sliding Board for People with Disability - สมงาม พิสิษฐ์; วงค์เจริญ ณีรนุช (Journal of Health Science of Thailand, 2021)
This study aimed to develop and assess the effectiveness of an innovative device for assisting people with disability on their routine movement. It was made of wood in the form of a sliding board. So far, 3 versions of the board were developed using PDCA process; and the latest version was tested in this study. The study samples were 17 persons with paralysis of the lowere extrimities. Data collection tools were a orm for collecting Barthel activity of daily living index and a quality of life questionnaires. The data were analyzed using descriptive statistics and pair sample t-test. The results showed that all 17 disability persons were able to use the device to assist their daily activities and reduce pressure sore. The Barthel activity of daily living index and quality of life scores show significant improvement (p<0.01). The innovative device was easy to use and carry; and was easily rotatable up. It should be widely promoted as a sliding device for people with paralysis of the lower extremities.